Effect of phosphorus doping on the performance of pin-type a-Si:H thin-film solar cells. (11th February 2018) - Son, Won Ho; Lee, Tae Yong; Choi, Sie Young; Jung, Daewoong
ABSTRACT: This article shows the characteristics of pin-type a-Si:H thin-film solar cells with various PH3 concentrations in the i-layer. A series of phosphorus doped a-Si:H films were fabricated by mixing PH3 and SiH4 with H2 during the i-layer deposition. The concentration of PH3 was varied in the range of 0–3650 ppm. By phosphorus doping of the i-layer, the properties of the i-layer were changed light doped n layer (n-), and we were able to improve all these electrical parameters (Voc, Jsc, and FF). Consequently, we achieved a higher conversion efficiency η than in conventional pin-type a-Si:H solar cells with undoped i-layer.